Manhaji Fiqh Learning and the Strengthening of Istinbath Reasoning among Mahasantri in Ma’had Aly (Journal Of Islamic Education And Pesantren, 2025)
This study aims to analyze the implementation of Manhaji Fiqh learning and its contribution to strengthening the istinbāṭ reasoning of mahasantri at Ma’had Aly Mamba’ul Ma’arif Denanyar Jombang. The research employs a qualitative approach with a phenomenological design to understand the academic experiences of students in the process of methodology-based fiqh learning. Data were collected through in-depth interviews, classroom observations, and documentation related to curriculum and learning practices. Data analysis was conducted through data reduction, categorization, and thematic interpretation, while data validity was ensured through source and method triangulation. The findings reveal that Manhaji Fiqh learning is implemented through the integration of traditional pesantren methods such as bandongan and lectures with dialogical approaches including discussions, question-and-answer sessions, and baḥṡ al-masā’il practices. The learning materials focus on the understanding of qawāʿid fiqhiyyah and uṣūl al-fiqh as methodological foundations for deriving Islamic legal rulings. The implementation of this learning model encourages a cognitive transformation among students from a purely textual understanding of fiqh toward a methodological approach in analyzing Islamic legal issues. Furthermore, active participation in the baḥṡ al-masā’il forum enhances students’ analytical and argumentative skills in the process of legal reasoning. Therefore, Manhaji Fiqh learning plays a strategic role in developing methodological competence and Islamic legal reasoning within the Ma’had Aly educational environment.